Las cuentas de ingresos y gastos y su incidencia en la ejecución presupuestaria de la estación experimental tropical pichilingue del INIAP Cantón Quevedo, periodo 2012 - Muñoz Ronquillo, Shirley Maribel (2013)
The present research contains general objective to determine the incidence of income and expense accounts in the budgetary implementation of Pichilingue Tropical Experiment Station, Canton Quevedo, and 2012 period. To determine the internal control processes and the level of budget execution it was carried out a special examination in order to assess the processes that take place in the income and expenditure. The special test was used as a tool to assess compliance with the internal control standards in the operations of the institution, taking into suggested by the author Hernan Cardoso Cuenca in his book " AUDITORIA DEL SECTOR SOLIDARIO " consideration , it permited possible to examine the internal control procedures used to determine the level of compliance of budget implementation . This research allowed detecting the differences existing in each audited level that has not allowed achieving a level of optimum performance. As a result of the investigation it was determined that the Station Experimental Tropical Pichilingue has a confidence level of 77 % in the internal control procedures of revenues and 80 % in the internal control procedures on the expenditure which shows that the development of internal control processes have a moderate level of risk.